Pupils’ Reflective Thinking and Self-Efficacy Level for Problem Solving - Dr. M N Kholid, Annisa Swastika, Evatias Nirmala, Swasti Maharani, Majid, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reflective thinking begins by pupils’ perplexity and re-evaluation for problem solving. In term of overcoming perplexity and another confusion, pupils’ beliefs and level of self-efficacy are necessary. The study conducted to address the impact of self-efficacy level into pupils reflective thinking for problem solving. The research is a qualitative study that describes data and facts without any manipulation. The research employed 149 pupils as subjects from 9 Senior High Schools in Central Java and East Java – Indonesia. The data collection consisted of questionnaire to categorize self-efficacy level, a test to explore pupils’ reflective thinking, and an in-depth interview to make sure the data of pupils’ reflective thinking. The data validation employed a triangulation technique. Different levels of pupils' self-efficacy indicate differences in reflective thinking in solving problems. We successfully concluded the higher self-efficacy level the more reflective thinking indictors fulfilled. In improving pupils’ reflective thinking ability, the educational practices must improve pupils’ self-efficacy by designed model learning or another instruments.